Bedside Matters: The Transformation of Canadian Nursing, 1900-1990 - McPherson, Kathryn (Canadian social history series, 2016)
Nursing embodies the seemingly timeless characteristics of feminine healing, caring, and nurturing, yet this archetypally female vocation also boasts a distinctive and complex history. Bedside Matters traces four generations of Canadian nurses to explore changes in who became nurses, what work they performed, and how they organized to defend their occupational interests. Whether in the apprenticeship method of the early twentieth century or in the present day restructuring of hospital work, the position of nurses within the health-care system has been structured by class, gender, and ethnic and racial relations. Located between the doctors and untrained or subsidiary patient-care attendants, nurses have struggled to define the boundaries of their occupation vis à vis other members of the health-care hierarchy, even as tensions between bedside and administrative nurses created divisions within nursing itself. Focusing on the daily labours of 'ordinary nurses', McPherson argues that the persisting sex-typing of nursing as women's work has meant that gender consistently complicated nursing's easy categorization as either professional or proletariat. Combining archival records and oral histories, the author shows how nurses, in their work, activities, and social and sexual attitudes, sought recognition as skilled workers in the health-care system. --Publisher's description

Gendered Pasts: Historical Essays in Feminity and Masculinity in Canada - McPherson, Kathryn; Morgan, Cecilia; Forestell, Nancy M. (Canadian social history series, 2015)
It is commonplace today to suggest that gender is socially constructed, that the roles women and men fulfill in their daily lives have been created and defined for them by society and social institutions. But how have men and women negotiated and navigated the gender roles that have been thrust upon them? With Gendered Pasts, Kathryn McPherson, Cecilia Morgan, and Nancy M. Forestell have collected eleven engaging essays that seek to answer this question in a wide-ranging exploration of specific gendered dimensions of nineteenth- and twentieth-century Canadian history.The contributors cover all manner of topics related to gender and history across Canada, including: female vagrancy; gambling, drinking, and sex; the role of the miner's wife; the portrayal of gay men; and the sharply defined role of nurses. Unusual in its breadth, Gendered Pasts is essential to the understanding of the various threads and themes in Canadian gender history. Previously published by Oxford University Press, . --Publisher's description
Keywords: Sex role -- Canada -- History -- 19th century